PENGARUH KEPERCAYAAN MEREK TERHADAP LOYALITAS MEREK SEPEDA MOTOR HONDA DI KOTA PONTIANAK - B11106052, Oktavianus Irvan (Jurnal Manajemen Update, 2014)
This research is motivated by business rivalry condition motor vehicle industry over time intensifies, so the company had to make a new marketing strategy in order to maintain and gain market share higher and wider. As for the issue of this study is whether the brand predictability, brand liking, brand competence, brand reputation, trust in the company influence on brand loyalty either simultaneously or each variable. In this study data were collected through questionnaire method against 100 respondents HONDA motorcycle product users in the city of Pontianak by using purposive sampling method to determine the respondents to each variable. Then the analysis of the data obtained in the form of quantitative analysis and qualitative analysis. Quantitative analysis includes validity and reliability, the classical assumption, hypothesis testing by F test and t test analysis and test the coefficient of determination (R2). The data analysis technique used is multiple linear regression analysis which serves to prove the research hypothesis. The data that have met the test of validity, reliability testing, and classical assumption processed to produce a regression equation as follows: Y = 0.274 + 0.218 X1 + 0.270 X2 + 0.238 X3 + 0.207 X4 X5 Results of the analysis found that five factors predictability brand, the brand preference, brand competence, brand reputation, and trust in the company has a positive and significant effect on brand loyalty. Hypothesis testing using t-test showed that the five independent variables studied was shown to significantly affect the dependent variables of brand loyalty. Then through the F test can be seen that the variable predictability brand, the brand preference, brand competence, brand reputation, and trust in a company jointly significant effect on brand loyalty. Figures adjusted R square of 0.532 indicates that 53.2 percent of variation in brand loyalty could be explained by the five independent variables used in the regression equation. While the remaining 46.8 percent is explained by other variables outside the five variables used in this study. Keywords: predictability of the brand, the brand preference, brand competence, brand reputation, trust in the company and brand loyalty